Pelatihan Pembuatan Media Interaktif Adobe Flash : Pada Pembelajaran Kurikulum Merdeka Belajar di Sekolah Dasar - Feri Tirtoni (Universitas PGRI Adi Buana Surabaya, 2023)
This community service activity aims to overcome the problem of lack of understanding and information from the school community on the development of information technology, especially Adobe Flash interactive media. The use of technology in learning can be an option to make media innovations that are new and become interesting material for students. One way to make learning interesting is by using learning media. The use of learning media in the teaching and learning process can generate new desires and interests, generate motivation and stimulation of learning activities, and even bring psychological effects on students. Because of the New Normal era and schools have implemented face-to-face learning, schools, in this case teachers, need to have innovative learning designs that are attractive but also effective. With this problem, the researchers held training on making Adobe Flash interactive media on the Merdeka curriculum which was held at SDN Keboananom